2020
DOI: 10.1007/s00223-020-00657-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Sleep Quality and Bone Outcomes in Older Adults: Findings from the Hertfordshire Cohort Study

Abstract: Sleep duration may be associated with risk of osteoporosis, with suggestions that too little or indeed too much sleep may be detrimental to bone health. In this study, we considered whether perceived sleep quality is also associated with bone health in older adults. We explored this association in a cohort of 443 older community-dwelling UK adults. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI); poor sleep quality was defined as > 5 on this score system. Bone density, shape and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
1
6
2
Order By: Relevance
“…Moreover, awakening from sleep through pain affects the mental state of the patients. The existing literature describes that women in Sweden, after a compression fracture of their spine, complained about sleep problems at night, woke up with severe pain, and many of them took sleeping pills for better rest [31]. We have not shown a statistically signi cant relationship between sleep length and QUALEFFO 41.…”
Section: Discussioncontrasting
confidence: 52%
“…Moreover, awakening from sleep through pain affects the mental state of the patients. The existing literature describes that women in Sweden, after a compression fracture of their spine, complained about sleep problems at night, woke up with severe pain, and many of them took sleeping pills for better rest [31]. We have not shown a statistically signi cant relationship between sleep length and QUALEFFO 41.…”
Section: Discussioncontrasting
confidence: 52%
“…Along with differences in PA, we also found differences in the relative time spent sleeping. A recent review suggested that shorter and longer sleepers are at greater risk of developing muscle failure and lower values of BMD, when considering sleep in isolation [ 67 , 68 ]. Conversely, when the whole 24 h day was considered, no relationship between sleep duration and musculoskeletal health was found.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30] In the current study, we have noted that taking sleeping pills deteriorates quality of life. These observations can be explained by an earlier study, which suggests that the use of sleeping pills in women may be associated with worse bone health and should be considered when reviewing older patients [29].…”
Section: Discussionmentioning
confidence: 95%
“…This study indicates that one of the factors related to the perception of general health is sleep. Poor quality of sleep (sleep disorders) may be associated with osteoporosis [28], by affecting the bone microarchitecture [29]. It is known that a good night's sleep is a key factor in maintaining quality of life.…”
Section: Discussionmentioning
confidence: 99%